Assessing the influence of repeated exposures and mental stress on human wayfinding performance in indoor environments using virtual reality technology. (January 2019) - Lin, Jing; Cao, Lijun; Li, Nan
Highlights: Participants took multiple trials to explore a virtual museum with or without a fire. Repeated exposure to the same space improved wayfinding performance of participants. Fire emergency negatively affected the wayfinding performance of participants. Repeated exposure diminished the negative impact of fire emergency. Effect of repeated exposures on wayfinding behavior became stable after a threshold. Abstract: This study aimed to examine the effect of repeated exposures to indoor environments on people's indoor wayfinding performance, both under normal condition and during fire emergency which could induce significant mental stress. Indoor wayfinding experiments were conducted in an immersive virtual museum developed using virtual reality technologies. Participants of the experiments were divided into three groups, who participated in one, two and three trials, respectively. Those who participated in more than one trial were given an interval of two weeks between two consecutive trials. Each trial of the experiment included a treasure hunting task and an egress task. Participants were presented with a virtual fire emergency during the egress task of their last trial. Data of wayfinding performance measures of the participants, as well as their physiological and emotional responses, sense of direction, wayfinding anxiety and simulator sickness were collected and analyzed. The results revealed significant positive impact of repeated exposure on participants' wayfinding performance, which resulted in a decrease in the time needed to complete the treasure hunting task. The results also revealed significant negative impact of mental stressed caused by the fire emergency on participants' wayfinding performance, which led to increased travel time and distance during egress. Such negative impact of stress, however, could be noticeably diminished by the repeated exposures, showing significant interaction effect between these two factors.